The effect of therapeutic rehabilitation exercises using an arterial occlusion device (A.C.A.) on ankle sprain injuries according to some immunological indicators in volleyball players. - Al-Safi, Prof. Dr. Asaad Adnan Aziz Al-Safi; Mutasher, L. Ali Ghanem Mutasher; Saleh, L. Sabah Mahdi (Sulaimani Journal for Humanities, 2018)
An athlete with an ankle injury needs a therapeutic approach to accelerate the return to his normal condition before the injury occurred and his return to the stadiums in an appropriate manner. One of the new and innovative methods for this purpose, through which we hope to obtain the desired results in returning the injured athlete to his normal condition faster than the usual and traditional cases used for treatment, is the use of the effect of therapeutic rehabilitation exercises using the arterial closure device (A.C.A) for ankle joint sprain injury according to some immune indicators in volleyball players. This is considered a new scientific method in treating and rehabilitating the injury that has not been used before in Iraq, as it is used immediately after the injury occurs, unlike the traditional methods known in the field of treatment and rehabilitation that depend on pressure, plastering, etc. This method is based on the results of anaerobic work by deliberately placing the working muscles of the lower limb (thigh muscles) under anaerobic conditions by creating ischemia (preventing the arterial blood from reaching the organ) through the use of the arterial closure device (A.C.A) to cause a state of blood ischemia. The arterial supply to the lower limb passes through the ankle joint, which is the target of this operation. The research objectives are to prepare special exercises using the arterial occlusion device (A.C.A.) to induce ischemia of the lower limb in volleyball players and to identify the effect of special exercises using the arterial occlusion device (A.C.A.) in the treatment and rehabilitation of ankle sprain according to the number of white blood cells (WBC) and immunoglobulin (IgG) and (IgM) in volleyball players. The most important conclusions are that the use of the arterial occlusion device has a positive effect in the treatment and rehabilitation of ankle sprain and there is a clear increase in the immune proteins IgG, IgM when the injury occurs directly in the research sample as a result of the defensive role it plays by increasing the activation of the immune system cells, which leads to the formation of a strong line of defense against the injury that the player may be exposed to.
Keywords: Therapeutic rehabilitation exercises; arterial occlusion device (ACA); ankle sprain; immune indicators; volleyball players